Bonding agent and preparation method thereof, and preparation method of electronic base material

By grafting modified polydimethylsiloxane on the surface of zeolite imidazole skeleton material, an organic-inorganic hybrid bonding agent was prepared, which solved the problem of insufficient bonding force between copper foil and insulating substrate in high-frequency and high-speed signal transmission, and achieved the effect of improving the anti-peel strength on low-rough copper foil.

CN119708500AActive Publication Date: 2025-03-28SHENZHEN QINGYAN ELECTRONIC TECH CO LTD
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
CN202510060158.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-15
Publication Date
2025-03-28
Estimated Expiration
2045-01-15

AI Technical Summary

Technical Problem

Under 5G electronic information technology, when high-frequency and high-speed signal transmission, the roughness of the copper foil interface has a significant impact on signal transmission, resulting in an increase in signal loss. The bonding force between the low-roughness copper foil and the insulating substrate is reduced, and the anti-peel strength is insufficient, which cannot meet the practical application requirements.

Method used

By mixing the zeolite imidazole backbone material with modified polydimethylsiloxane and reacting under an inert atmosphere, a zeolite imidazole backbone material with surface grafted modified polydimethylsiloxane was prepared, and an organic-inorganic hybrid bonding agent was prepared. This bonding agent can not only form coordination bonding with copper foil, but also form chemical and physical adsorption with the surface of the insulating substrate, thereby enhancing the bonding force between the copper foil and the insulating substrate.

Benefits of technology

By using this bonding agent, the bonding force between the copper foil and the insulating substrate can be significantly improved while using low-roughness copper foil, meeting the application requirements of high-frequency and high-speed signal transmission, and improving the peel strength of the copper clad plate.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119708500A_ABST
    Figure CN119708500A_ABST
Patent Text Reader

Abstract

The invention discloses a bonding agent and a preparation method thereof, and a preparation method of an electronic substrate. The preparation method of the bonding agent comprises the following steps: mixing a zeolite imidazate framework material with modified polydimethylsiloxane, adding a catalyst, and reacting in an inert atmosphere to obtain the zeolite imidazate framework material of which the surface is grafted with the modified polydimethylsiloxane. The bonding agent provided by the invention can solve the current situation that the binding force between a copper foil and an insulating substrate of a traditional copper-clad plate is insufficient, effectively improves the anti-stripping strength of the copper foil, and provides a solid guarantee for the application of a high-performance copper-clad plate in the fields of high-frequency and high-speed electronic circuits and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of electronic materials, and in particular to a bonding agent and a preparation method thereof, and a preparation method of an electronic substrate. Background Art

[0002] With the rapid development of 5G electronic information technology, electronic circuit substrates (mainly copper-clad laminates) are moving towards high frequency and high speed. When high-frequency and high-speed signals are transmitted, signal loss will occur, and the higher the frequency, the greater the loss. The loss mainly comes from dielectric loss and conductor loss. Especially in the 30 GHz~300 GHz band, the skin effect makes the copper foil interface roughness have a significant impact on signal transmission.

[0003] Therefore, developing a roughening-free or low-roughening copper surface treatment process has become a new topic for high-frequency and high-speed electronic circuit manufacturing under 5G communication technology. However, low roughness will lead to a decrease in the bonding strength between the copper foil and the insulating substrate, which in turn will cause a serious decrease in the peeling strength of the copper clad laminate, making it still unable to meet the requirements of practical applications. Therefore, while using a roughening-free or low-roughening copper surface, how to enhance the bonding strength between the copper foil and the insulating substrate has become a difficult problem that needs to be overcome. Summary of the invention

[0004] In view of this, the present application provides a bonding agent and a preparation method thereof, and a preparation method of an electronic substrate.

[0005] The first aspect of the present application provides a method for preparing a bonding agent, comprising: The zeolite imidazolate skeleton material is mixed with modified polydimethylsiloxane, a catalyst is added, and the mixture is reacted under an inert atmosphere to obtain the zeolite imidazolate skeleton material with the modified polydimethylsiloxane grafted on the surface.

[0006] In some embodiments, the catalyst includes at least one of dibutyltin dilaurate tetrabutyl titanate, stannous octoate, or triethylamine.

[0007] In some embodiments, the modified polydimethylsiloxane is a polydimethylsiloxane with a functional group modified at the end of the chain segment, and the functional group includes at least one of a thiol group, an amino group, an aminopropyl group, a vinyl group, a hydroxyl group, a hydroxymethyl group or a glycidyl ether.

[0008] In some embodiments, the modified polydimethylsiloxane includes at least one of mercaptopropyl-terminated polydimethylsiloxane, bis(3-aminopropyl)-terminated polydimethylsiloxane, vinyl-terminated dimethylpolysiloxane, hydroxy silicone oil, diglycidyl ether-terminated polydimethylsiloxane, hydroxyalkyl-di-terminated polydimethylsiloxane, polydimethylsiloxane alcohol hydroxystearate, monoglycidyl ether-terminated polydimethylsiloxane, aminopropyl-terminated polydimethylsiloxane, hydroxymethyl-terminated polydimethylsiloxane, or (mercapto)methylsiloxane-dimethylsiloxane copolymer.

[0009] In some embodiments, the modified polydimethylsiloxane is a polydimethylsiloxane with a thiol group modified at the end of the chain segment.

[0010] In some embodiments, the amount of the modified polydimethylsiloxane is 15 wt % to 30 wt % of the zeolite imidazolate framework material, and the amount of the catalyst is 2 wt % to 6 wt % of the modified polydimethylsiloxane.

[0011] In some embodiments, the reaction temperature is 60° C. to 100° C., and the reaction time is 5 h to 8 h.

[0012] In some embodiments, the preparation method of the zeolite imidazolate framework material comprises: reacting an imidazole organic compound with a zinc salt at 60°C~130°C for 2h~6h, and the molar ratio of the imidazole organic compound to the zinc salt is (2~3):1.

[0013] The second aspect of the present application provides a bonding agent prepared according to the above preparation method.

[0014] The third aspect of the present application provides a method for preparing an electronic substrate, comprising: coating the above-mentioned bonding agent on the surface of a copper foil, and pressing the copper foil coated with the bonding agent to a substrate.

[0015] The present application obtains an organic-inorganic hybrid bonding agent by grafting modified polydimethylsiloxane on the surface of zeolite imidazolate skeleton material. The bonding agent can form coordination bonding with inorganic metal (i.e. copper foil) on the one hand, and can form chemical action and physical adsorption action with the surface of organic insulating substrate on the other hand, so as to establish a strong connection system between copper foil and insulating substrate, so as to ensure the bonding force between copper foil and insulating substrate while using low roughness copper foil. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 A schematic flow chart of a method for preparing a bonding agent provided in one embodiment of the present application. DETAILED DESCRIPTION

[0017] The embodiments of the present application are described in detail below. The embodiments described below with reference to the accompanying drawings are exemplary and are only used to explain the present application, and cannot be understood as limiting the present application. The reagents and materials described in the following embodiments can all be obtained from commercial sources.

[0018] See also Figure 1 The present application provides a method for preparing a bonding agent, comprising: mixing a zeolite imidazolate skeleton material with modified polydimethylsiloxane (i.e., modified PDMS), adding a catalyst, and reacting under an inert atmosphere to obtain a zeolite imidazolate skeleton material with surface grafted modified polydimethylsiloxane.

[0019] The bonding agent provided in the present application can, on the one hand, coordinately bond with the copper atoms on the surface of the copper foil of the copper clad laminate through the zeolite imidazolate skeleton material (i.e., ZIF-8 nanoparticles); on the other hand, the grafted modified polydimethylsiloxane chain segment has flexibility and heat resistance, and can form chemical and physical adsorption effects with the surface of the insulating substrate of the copper clad laminate, so that the bonding agent builds a strong connection system between the copper foil and the insulating substrate, which satisfies the requirement of using low-roughness copper foil while ensuring the bonding force between the copper foil and the insulating substrate.

[0020] In some embodiments, the preparation method of the zeolite imidazolate framework material comprises: reacting an imidazole organic compound with a zinc salt at 60° C. to 130° C. for 2 h to 6 h, and the molar ratio of the imidazole organic compound to the zinc salt is (2 to 3):1.

[0021] For example, the imidazole organic compound and the zinc salt can react at a temperature of 60°C, 70°C, 80°C, 90°C, 100°C, 110°C, 120°C, 130°C or any value within the range formed by any two of the above values; the reaction time of the imidazole organic compound and the zinc salt can be 2h, 3h, 4h, 5h, 6h or any value within the range formed by any two of the above values; the molar ratio of the imidazole organic compound to the zinc salt can be 2:1, 2.5:1, 3:1 or any value within the range formed by any two of the above values. Controlling the synthesis conditions of the zeolite imidazolate framework material within the above range is conducive to the successful preparation of the zeolite imidazolate framework material.

[0022] In some embodiments, the imidazole organic compound may be at least one of dimethylimidazole or benzimidazole, and the zinc salt may be one or more of zinc nitrate, zinc sulfate, zinc chloride, zinc acetate or zinc citrate.

[0023] In some embodiments, the modified polydimethylsiloxane is a polydimethylsiloxane with functional groups modified at the ends of the segments, and the functional groups include at least one of mercapto, amino, aminopropyl, vinyl, hydroxyl, hydroxymethyl or glycidyl ether. These functional groups help to increase the chemical and physical adsorption between the siloxane segments and the insulating substrate, so as to enhance the connection strength between the bonding agent and the surface of the insulating substrate.

[0024] In some embodiments, the modified polydimethylsiloxane includes at least one of mercaptopropyl-terminated polydimethylsiloxane, bis(3-aminopropyl)-terminated polydimethylsiloxane, vinyl-terminated dimethylpolysiloxane, hydroxy silicone oil, diglycidyl ether-terminated polydimethylsiloxane, hydroxyalkyl-terminated polydimethylsiloxane, polydimethylsiloxane alcohol hydroxystearate, monoglycidyl ether-terminated polydimethylsiloxane, aminopropyl-terminated polydimethylsiloxane, hydroxymethyl-terminated polydimethylsiloxane, or (mercapto)methylsiloxane-dimethylsiloxane copolymer.

[0025] In some embodiments, the modified polydimethylsiloxane is a polydimethylsiloxane with a thiol group modified at the end of the chain segment. The modified polydimethylsiloxane is preferably a polydimethylsiloxane with a thiol group modified at the end of the chain segment. Compared with other functional groups, the thiol group has strong chemical activity and can react chemically with active groups such as unsaturated bonds in the insulating substrate of the copper clad laminate to form strong interactions such as covalent bonds, thereby having a better effect on enhancing the peel strength of the copper foil of the copper clad laminate.

[0026] In some embodiments, the catalyst includes at least one of dibutyltin dilaurate, tetrabutyl titanate, stannous octoate, or triethylamine.

[0027] In some embodiments, the amount of modified polydimethylsiloxane is 15 wt% to 30 wt% of the zeolite imidazolate framework material, and the amount of the catalyst is 2 wt% to 6 wt% of the modified polydimethylsiloxane. For example, the amount of modified polydimethylsiloxane can be 15 wt%, 18 wt%, 20 wt%, 23 wt%, 25 wt%, 28 wt%, 30 wt% of the zeolite imidazolate framework material, or any value within the range formed by any two of the above values; the amount of the catalyst can be 2 wt%, 3 wt%, 4 wt%, 5 wt%, 6 wt% of the modified polydimethylsiloxane, or any value within the range formed by any two of the above values.

[0028] In some embodiments, the temperature of the reaction of the zeolite imidazolate framework material with the modified polydimethylsiloxane is 60°C to 100°C, and the reaction time is 5h to 8h. For example, the reaction temperature can be 60°C, 70°C, 80°C, 90°C, 100°C, or any value within the range formed by any two of the above values; the reaction time can be 5h, 5.5h, 6h, 6.5h, 7h, 7.5h, 8h, or any value within the range formed by any two of the above values. Controlling the reaction temperature and reaction time of the zeolite imidazolate framework material with the modified polydimethylsiloxane within the above range is conducive to the successful grafting of the modified polydimethylsiloxane onto the surface of the zeolite imidazolate framework material.

[0029] The present application also provides a bonding agent prepared according to the above preparation method.

[0030] A method for preparing an electronic substrate comprises: coating a bonding agent on the surface of a copper foil, and pressing the copper foil coated with the bonding agent to a substrate.

[0031] In some embodiments, before the bonding agent is applied, the bonding agent is dispersed in a solvent, and the bonding agent has a dispersion concentration of 10 wt% to 15 wt%. For example, the dispersion concentration may be 10 wt%, 11 wt%, 12 wt%, 13 wt%, 14 wt%, 15 wt%, or any value within the range formed by any two of the above values.

[0032] In some embodiments, the copper foil coated with the bonding agent and the substrate may be laminated.

[0033] The technical solution of the present application is further explained below in conjunction with specific implementation methods.

[0034] Example 1 Dimethylimidazole and zinc nitrate were dissolved in a methanol solution at a molar ratio of 2:1, and then stirred at 120°C for 3 hours. After the reaction was completed, centrifugation and washing were performed to obtain pure ZIF-8 nanoparticles.

[0035] The ZIF-8 nanoparticles were uniformly dispersed in a toluene solution, to which mercaptopropyl-terminated polydimethylsiloxane and dibutyltin dilaurate were pre-added. The amount of mercaptopropyl-terminated polydimethylsiloxane was 20wt% of the ZIF-8 nanoparticles, and the amount of dibutyltin dilaurate was 3wt% of the mercaptopropyl-terminated polydimethylsiloxane. The reaction was heated at 80°C for 6h under the protection of argon to obtain a bonding agent.

[0036] The application steps of bonding agent in copper clad laminate are as follows: S1. Pre-treat the copper foil: ultrasonically clean the copper foil in acetone and ethanol in sequence to thoroughly remove oil stains and impurities on the surface of the copper foil. After cleaning, dry the copper foil for later use.

[0037] S2. Applying bonding agent: Evenly disperse the prepared bonding agent in a volatile isopropanol solvent. The dispersion concentration of the bonding agent in isopropanol is 10wt%. Spray the bonding agent solution on the surface of the pretreated copper foil. After coating, dry it at 80°C for 30 minutes to completely evaporate the isopropanol solvent. The bonding agent forms a uniform and stable coating on the surface of the copper foil.

[0038] S3. Lamination with insulating substrate: The copper foil coated with bonding agent is laminated with the insulating substrate, and the pressing is performed for 150 minutes under the conditions of vacuum degree of 3Kpa, pressure of 8MPa and temperature of 360°C, so that the insulating substrate and the copper foil are tightly combined to finally form a copper clad laminate.

[0039] Example 2 Dimethylimidazole and zinc nitrate were dissolved in a methanol solution at a molar ratio of 3:1, and then stirred at 120°C for 4 hours. After the reaction was completed, centrifugation and washing were performed to obtain pure ZIF-8 nanoparticles.

[0040] The ZIF-8 nanoparticles were uniformly dispersed in a toluene solution, to which mercaptopropyl-terminated polydimethylsiloxane and dibutyltin dilaurate were pre-added. The amount of mercaptopropyl-terminated polydimethylsiloxane was 30wt% of the ZIF-8 nanoparticles, and the amount of dibutyltin dilaurate was 6wt% of the mercaptopropyl-terminated polydimethylsiloxane. The reaction was heated at 80°C for 8h under the protection of argon to obtain a bonding agent.

[0041] The application steps of bonding agent in copper clad laminate are as follows: S1. Pre-treat the copper foil: ultrasonically clean the copper foil in acetone and ethanol in sequence to thoroughly remove oil stains and impurities on the surface of the copper foil. After cleaning, dry the copper foil for later use.

[0042] S2. Applying bonding agent: Evenly disperse the prepared bonding agent in a volatile isopropanol solvent. The dispersion concentration of the bonding agent in isopropanol is 15wt%. Spray the bonding agent solution on the surface of the pretreated copper foil. After coating, dry it at 100°C for 20 minutes to completely evaporate the isopropanol solvent. The bonding agent forms a uniform and stable coating on the surface of the copper foil.

[0043] S3. Lamination with insulating substrate: The copper foil coated with bonding agent is laminated with the insulating substrate, and the pressing is carried out for 120 minutes under the conditions of vacuum degree of 3Kpa, pressure of 7MPa and temperature of 380°C, so that the insulating substrate and the copper foil are tightly combined to finally form a copper clad laminate.

[0044] Example 3 Dimethylimidazole and zinc nitrate were dissolved in a methanol solution at a molar ratio of 2:1, and then stirred at 120°C for 3 hours. After the reaction was completed, centrifugation and washing were performed to obtain pure ZIF-8 nanoparticles.

[0045] The ZIF-8 nanoparticles were uniformly dispersed in a toluene solution, to which bis(3-aminopropyl)-terminated polydimethylsiloxane and dibutyltin dilaurate were pre-added. The amount of bis(3-aminopropyl)-terminated polydimethylsiloxane was 20wt% of the ZIF-8 nanoparticles, and the amount of dibutyltin dilaurate was 3wt% of the bis(3-aminopropyl)-terminated polydimethylsiloxane. The reaction was heated at 80°C for 6h under the protection of argon to obtain a bonding agent.

[0046] The application steps of bonding agent in copper clad laminate are as follows: S1. Pre-treat the copper foil: ultrasonically clean the copper foil in acetone and ethanol in sequence to thoroughly remove oil stains and impurities on the surface of the copper foil. After cleaning, dry the copper foil for later use.

[0047] S2. Applying bonding agent: Evenly disperse the prepared bonding agent in a volatile isopropanol solvent. The dispersion concentration of the bonding agent in isopropanol is 10wt%. Spray the bonding agent solution on the surface of the pretreated copper foil. After coating, dry it at 80°C for 30 minutes to completely evaporate the isopropanol solvent. The bonding agent forms a uniform and stable coating on the surface of the copper foil.

[0048] S3. Lamination with insulating substrate: The copper foil coated with bonding agent is laminated with the insulating substrate, and the pressing is performed for 150 minutes under the conditions of vacuum degree of 3Kpa, pressure of 8MPa and temperature of 360°C, so that the insulating substrate and the copper foil are tightly combined to finally form a copper clad laminate.

[0049] Example 4 Dimethylimidazole and zinc nitrate were dissolved in a methanol solution at a molar ratio of 3:1, and then stirred at 120°C for 4 hours. After the reaction was completed, centrifugation and washing were performed to obtain pure ZIF-8 nanoparticles.

[0050] The ZIF-8 nanoparticles were uniformly dispersed in a toluene solution, to which hydroxyalkyl di-terminated polydimethylsiloxane and dibutyltin dilaurate were pre-added. The amount of hydroxyalkyl di-terminated polydimethylsiloxane was 30wt% of the ZIF-8 nanoparticles, and the amount of dibutyltin dilaurate was 6wt% of the hydroxyalkyl di-terminated polydimethylsiloxane. The reaction was heated at 80°C for 8h under the protection of argon to obtain a bonding agent.

[0051] The application steps of bonding agent in copper clad laminate are as follows: S1. Pre-treat the copper foil: ultrasonically clean the copper foil in acetone and ethanol in sequence to thoroughly remove oil stains and impurities on the surface of the copper foil. After cleaning, dry the copper foil for later use.

[0052] S2. Applying bonding agent: Evenly disperse the prepared bonding agent in a volatile isopropanol solvent. The dispersion concentration of the bonding agent in isopropanol is 15wt%. Spray the bonding agent solution on the surface of the pretreated copper foil. After coating, dry it at 100°C for 20 minutes to completely evaporate the isopropanol solvent. The bonding agent forms a uniform and stable coating on the surface of the copper foil.

[0053] S3. Lamination with insulating substrate: The copper foil coated with bonding agent is laminated with the insulating substrate, and the pressing is carried out for 120 minutes under the conditions of vacuum degree of 3Kpa, pressure of 7MPa and temperature of 380°C, so that the insulating substrate and the copper foil are tightly combined to finally form a copper clad laminate.

[0054] Examples 1 to 4 use the same copper foil and insulating substrate to make copper clad laminates.

[0055] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that in Comparative Example 1, the mercaptopropyl-terminated polydimethylsiloxane is replaced with polydimethylsiloxane, as shown in Table 1 and Table 2 for details.

[0056] <Performance Test> The test method for peel strength is as follows: Sample preparation: Cut a sample with a length of 120 mm and a width of 70 mm from the area 2.54 mm above the edge of the laminated copper clad board, stick an anti-corrosion tape on the sample, and use ferric chloride etching solution to make three test strips with a width of 3.18 mm and a length of 100 mm in the sample area.

[0057] Sample measurement: Use a universal testing machine, with the copper foil side of the test strip facing up, align the test strip with the center of the sample holder, place the pinhole plate on the test strip, place the clamping head in the hole, align the copper foil strip with the inclined slot, clamp the copper foil strip with the sample clamp, make the peeling direction 90 degrees to the insulating substrate, and start peeling at a rate of 50.8mm / min.

[0058] Peel strength = minimum peel force / sample width.

[0059] The peel strength test of Examples 1 to 4 and Comparative Example 1 was performed according to the above method. The test results are shown in Table 2.

[0060] Table 1 Table 2 It can be seen from Table 1 and Table 2 that the bonding agent provided in the present application enables the copper foil of the copper clad laminate and the insulating substrate to have good bonding force and high peeling strength.

[0061] Compared with comparative example 1, example 1 uses modified polydimethylsiloxane. There is a chemical reaction and physical adsorption effect between the siloxane segment of the modified polydimethylsiloxane and the insulating substrate, which can enhance the peeling strength between the copper foil and the insulating substrate.

[0062] By comparing Example 1 with Example 3 and Example 2 with Example 4, it can be seen that when the end of the chain segment of the modified polydimethylsiloxane contains a mercapto functional group, the mercapto functional group enhances the interaction between the bonding agent and the insulating substrate, thereby making the peeling strength between the copper foil and the insulating substrate higher.

[0063] The above implementation modes are only used to illustrate the technical solutions of the present application and are not intended to limit the present application. Although the present application is described in detail with reference to the above implementation modes, a person skilled in the art should understand that the technical solutions of the present application may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present application.

Claims

1. A method for preparing a bonding agent, characterized in that: include: The zeolite imidazolate skeleton material is mixed with modified polydimethylsiloxane, a catalyst is added, and the mixture is reacted under an inert atmosphere to obtain the zeolite imidazolate skeleton material with the modified polydimethylsiloxane grafted on the surface.

2. The method for preparing a bonding agent according to claim 1, characterized in that: The catalyst includes at least one of dibutyltin dilaurate, tetrabutyl titanate, stannous octoate or triethylamine.

3. The method for preparing a bonding agent according to claim 1, characterized in that: The modified polydimethylsiloxane is a polydimethylsiloxane with functional groups modified at the ends of the chain segments, and the functional groups include at least one of mercapto, amino, aminopropyl, vinyl, hydroxyl, hydroxymethyl or glycidyl ether.

4. The method for preparing a bonding agent according to claim 1, characterized in that: The modified polydimethylsiloxane includes at least one of mercaptopropyl-terminated polydimethylsiloxane, bis(3-aminopropyl)-terminated polydimethylsiloxane, vinyl-terminated dimethylpolysiloxane, hydroxy silicone oil, diglycidyl ether-terminated polydimethylsiloxane, hydroxyalkyl-di-terminated polydimethylsiloxane, polydimethylsiloxane alcohol hydroxystearate, monoglycidyl ether-terminated polydimethylsiloxane, aminopropyl-terminated polydimethylsiloxane, hydroxymethyl-terminated polydimethylsiloxane or (mercapto)methylsiloxane-dimethylsiloxane copolymer.

5. The method for preparing a bonding agent according to claim 3, characterized in that: The modified polydimethylsiloxane is a polydimethylsiloxane with a thiol group modified at the end of the chain segment.

6. The method for preparing a bonding agent according to claim 1, characterized in that: The amount of the modified polydimethylsiloxane is 15 wt% to 30 wt% of the zeolite imidazolate framework material, and the amount of the catalyst is 2 wt% to 6 wt% of the modified polydimethylsiloxane.

7. The method for preparing a bonding agent according to claim 1, characterized in that: The reaction temperature is 60°C to 100°C, and the reaction time is 5h to 8h.

8. The method for preparing a bonding agent according to claim 1, characterized in that: The preparation method of the zeolite imidazole ester framework material comprises: reacting an imidazole organic compound with a zinc salt at 60° C. to 130° C. for 2 h to 6 h, wherein the molar ratio of the imidazole organic compound to the zinc salt is (2 to 3):

1.

9. A bonding agent, characterized in that The bonding agent is prepared according to the preparation method according to any one of claims 1-8.

10. A method for preparing an electronic substrate, characterized in that: include: The bonding agent according to claim 9 is applied to the surface of a copper foil, and the copper foil coated with the bonding agent is pressed against a substrate.

Citation Information

Patent Citations

  • Pluridentate macromolecular bonding agent and preparation method thereof

    CN105503756A

  • Polydopamine modified hydrocarbon composition-based prepreg and copper clad plate prepared by using same

    CN109867914A

  • Novel high-frequency high-speed flexible copper-clad plate as well as preparation method and application thereof

    CN113365426A

  • Preparation process for reducing thermal expansion coefficient of copper-clad plate

    CN115816978A

  • Copper surface layer bonding agent and preparation method and application thereof

    CN117279238A